Motor performance in male youth soccer players: a systematic review of longitudinal studies - Abarghoueinejad, M.; Baxter-Jones, A. D.; Gomes, T. N.; Barreira, D.; Maia, J. (Sports, 2021)
The aim of this systematic review was to identify and synthesize the available information regarding longitudinal data addressing young soccer players` motor performance changes. Following the Preferred Reporting Items for Systematic and Meta-analyses (PRISMA) statement, literature searches were performed in three databases: PubMed, ISI Web of Science and SCOPUS. The following descriptors were used: football, soccer, youth, young, player, athlete, physical performance, motor performance, longitudinal. The inclusion criteria were original articles in English with longitudinal data of young males (aged 10-18 years), with the aim to investigate motor performance serial changes. The initial search returned 211 records, and the final sample comprised 32 papers. These papers covered the European continent, and used mixed and pure longitudinal design with variation in sample size and age range. The reviewed studies tended to use different tests to assess the motor performance and aimed to identify changes in motor performance in several ways. In general, they indicated motor performance improvements with age, with a marked influence of biological maturity, body composition, and training stimuli. This review highlights the need for coaches and stakeholders to consider players` motor performance over time whilst considering biological maturation, biological characteristics, and training stimuli.